The Role of Motivation and Work Discipline Analysis on Auto2000 Cirebon Employee Performance - Achmad Nauval Gibran; Ade Solahudin (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the influence of work motivation and work discipline on the performance of Auto2000 Cirebon employees, both partially and simultaneously. The study used an associative quantitative approach with a population of 250 permanent and contract employees of Auto2000 Cirebon, and a sample of 152 respondents determined through proportionate stratified random sampling. Primary data were collected through a Likert scale questionnaire (1–5) compiled based on 30 indicators of work motivation, work discipline, and employee performance variables, while secondary data were obtained from the company's internal reports and relevant previous studies. Data analysis was carried out using the PLS-SEM method with SmartPLS 4, through testing of the outer model (convergent validity, discriminant validity, and reliability) and inner model (multicollinearity, R-square, goodness of fit, and hypothesis testing). The results showed that work motivation had a negative and significant effect on employee performance with a path coefficient of -0.713 and a p-value of 0.000, while work discipline did not have a significant effect on employee performance with a p-value of 0.289. Simultaneously, work motivation and work discipline explained 48.6% of the variation in employee performance (R-square = 0.486), with the remaining 51.4% influenced by other variables outside the study model. These findings indicate an anomalous phenomenon in which the form of motivation applied has the potential to cause work pressure or burnout, suggesting that companies need to evaluate the design of their motivation systems and consider other factors such as work stress, job satisfaction, and leadership style.